Cavitation in epoxies under composite-like stress states. (March 2018) - Neogi, Anupam; Mitra, Nilanjan; Talreja, Ramesh
Abstract: In a previous study (Asp et al., 1995) the experimentally observed low strains to transverse tensile failure of unidirectional (UD) polymer matrix composites were explained as an effect of triaxial (composite- like) stress state in the epoxy matrix. Assuming cavitation as an underlying mechanism for brittle cracking under triaxial stress states, a dilatation energy density based criterion was put forth (Asp et al., 1996) and was shown to predict well the transverse failure of epoxy based UD composites (Asp et al., 1996). The assumption of cavitation in the epoxy matrix has hitherto not been supported by a mechanism study. The current study attempts to provide a systematic clarification of the cavitation mechanism by molecular dynamic simulation. By imposing uniaxial, equi-biaxial and equi-triaxial tension on a simulation cell of a crosslinked epoxy, the degrees of cavitation at various stages of the stress- strain response are revealed. The results show that triaxiality of the stress states is a governing factor in cavitation of epoxies.